INFLUENCE OF UNCERTAINTY FACTORS ON ROMANIA’S ECONOMIC CAPACITY ASSESSED THROUGH FINANCIAL CONTRIBUTION INDICATORS - Monica Laura ZLATI; Costinela FORTEA; Svetlana MIHAILA (Economica, 2022)
Economic capacity is a key element in shaping public policies, with a key role both in forecasting the elements of accounting, fiscal and monetary policy and in carrying out macroand micro-economic strategies. We aim to analyse the benchmarks on economic capacity through the predictable characteristics of economic and financial impact indicators and to determine the size of economic capacity sensitive to uncertainty through an economic model and evolution clusters for VAT and gross value added in relation to the elements of the structure of the economy at a given time. The results are useful for economic decision- makers to assess the necessary changes in accounting, fiscal and monetary policy in order to stabilize economic capacity at an optimally representative level for the current stage of economic development.